PENGUATAN AKHLAK MELALUI FULL DAY SCHOOL DALAM PERSPEKTIF PENDIDIKAN ISLAM - M. Anwar Djaelani; Faridi; Tobroni (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study aims to analyze the relevance of the full day school system in strengthening students' morals based on the perspective of Islamic education. The background of this research is based on the increasing challenges of moral degradation of students in the digital era which is characterized by various forms of disciplinary violations, low religious character, and weak behavioral supervision. In this context, full day school is seen as an alternative education system that allows schools to conduct character development more intensively and sustainably. This research uses a qualitative approach with the type of library research. Data was obtained through the study of various scientific journals, books, and academic documents relevant to the theme of Islamic education, full day school, and strengthening students' morals. Data analysis was carried out using content analysis techniques through the stages of data reduction, categorization, interpretation, and conclusion drawn. The results of the study show that the full day school system has a strong relevance to the principles of Islamic education through the application of teacher example, religious habituation, moral supervision, and integration of academic education with moral education. In addition to having a positive impact on the formation of religious character, discipline, and responsibility of students, this system also faces a number of challenges such as physical and mental fatigue of students, limited school facilities, and reduced interaction between students and families. This research produces a conceptual model of moral strengthening based on full day school which consists of teacher examples, religious habituation, moral supervision, and integration of Islamic educational values in all educational activities in schools.